Had + Have : une étrange construction grammaticale - Patrice Larroque (Anglophonia)
Contemporary English syntax does not allow redundant constructions like double superlatives, repeated negatives, or combinations of modals. There is, however, an example of verbal construction in the form of a “double perfect" (i.e. had have + V-en) which appears in informal speech instead of a regular pluperfect to express modal remoteness. It is a rather unusual construction in that had is followed by a bare infinitive, not a past participle. In this type of combination, which is not a recent grammatical innovation, it is questionable whether had have (had’ve) should be regarded as a compound auxiliary made of two forms of have, or as two distinct auxiliaries referring each to a distinct operation. The use of had have in counterfactuals explains why the analysis first deals with “modal had” and the nontemporal preterite verb forms in Modern English usage. I then describe current nonstandard productions containing had have in an attempt to define the values of the constituents and the function of this auxiliary construction.